Assessment of nutritional status of oncology patients at hospital admission: A Portuguese real-world study - Trabulo, Carolina; Lopes, Joana; da Silva Dias, David; Gramaça, João; Fernandes, Isabel; Gameiro, Rita; Pina, Idília; Mäkitie, Antti; Ottery, Faith; Ravasco, Paula (Frontiers in Nutrition, 2022)
BACKGROUND Nutritional status in patients with cancer has a determining role in the evolution of the disease and tolerance to treatments. Stage of undernutrition is a major source of morbidity and mortality in cancer patients and its presence can limit patient response to the best therapies if nutritional issues are not appropriately addressed and managed. The aim of the present study was to stratify the nutritional risk and characterize the nutritional status at admission in an Oncology Department. METHODS This is an observational study in 601 cancer out-patients, assessed at admission in a Medical Oncology Department from November 2016 to February 2020. All patients were considered eligible for inclusion, except non-compliant and/or comatose. Nutritional status was assessed using PG-SGA, BMI classified with the WHO criteria and calculation of the percentage of weight loss in the previous 3-6 months. RESULTS Total of 561 patients (303 F: 258 M; mean age 65±13 years) were included. One-third of the patients, n=191/561(34%), lost 6% of their weight in the month prior to admission and 297/561(53%) patients lost 10.2% of weight in the previous 6 months. Mean BMI was 24.1±5.8 kg/m2; n=280/561(50%) patients had regular weight by WHO criteria. Regarding food intake in the last month, n=331/561(59%) patients reported eating less as compared to the usual. As for physical examination, n=303/561(54%) had moderate/severe deficits of muscle and adipose compartments. PG-SGA identified 499/561(89%) patients as moderately/severely malnourished, and 466/561 (83%) patients scored ≥9 points, thus having critical need for nutritional support. We also found that 15% of patients scored >4 points, indicating need for directed therapy for symptom control and only 1% punctuated<2 points, maintenance nutritional counseling. CONCLUSION in this oncological setting, a high proportion of patients were nutritionally- at-risk or with moderate/severe malnutrition. The large majority of patients in this study presented a critical need for nutritional intervention. These findings in consecutive patients over a 4-year time period, consubstantiate the need for integrated assessment of nutritional status at patient referral. This will allow early and proactive nutrition care, which is desired to prevent or reverse further deterioration of the condition and to optimize treatment administration.